Diffusion coefficients from resonant interactions with electrostatic electron cyclotron harmonic waves - Tripathi A.K.; Singhal R.P. (My University, 2025)
Pitch-angle diffusion coefficients have been calculated for resonant interaction with electrostatic electron cyclotron harmonic (ECH) waves using quasilinear diffusion theory. Unlike previous calculations, the parallel group velocity has been included in this study. Further, ECH wave intensity is expressed as a function of wave frequency and wave normal angle with respect to ambient magnetic field. It is found that observed wave electric field amplitudes in Earth's magnetosphere are sufficient to set electrons on strong diffusion in the energy ranges of a few hundred eV. However, the required amplitudes are larger than the observed values for keV electrons and higher by about a factor of 3 compared to past calculations. Required electric field amplitudes are smaller at larger radial distances. It is concluded that ECH waves are responsible for diffuse auroral precipitation of electrons with energies less than about 500 eV. © 2009 American Institute of Physics.